DO YOU SEE THAT WE SEE; WHAT THE CONSTRAINTS AND BARRIERS TO MOBILE WALLETS IN INDONESIA - Halim Dwi Putra, Endang Siti Astuti, Andriani Kusumawati, Yusri Abdillah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Along with the times and technology, more and more changes occur in everyday life. One of them is about the use of electronic money. People do not need cash money anymore. Cash money has turned digital. It is called a mobile wallet. The use of mobile wallets is increasingly popular in Indonesia and is very growing today especially supported by the global pandemic situation lately. According to preliminary research, there are many complaints about the use of mobile wallets at this time, this is the main reason for this research. An online survey via Google form was conducted for mobile wallet users in Indonesia regarding the constraints and barriers experienced when using mobile wallets. The survey results found several constraints and barriers faced by the 480 respondents who answered. The results of the study can help mobile wallets companies to know factors that are relevant to the rise adoption of technology within the context of merchant and producer mobile wallets in Indonesia